2018
DOI: 10.18203/2320-1770.ijrcog20180894
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective study on the effect of Body Mass Index (BMI) on maternal and neonatal outcome

Abstract: Background: Obesity has become health problem worldwide. Prevalence of obesity has increased globally with more incidence observed in female than male. Objective of present study was assessment of maternal outcome in term of associated medical disorder and mode of delivery and assessment of neonatal outcome.Methods: The retrospective study performed at Nowrosjee Wadia Maternity Hospital, a tertiary care centre between 1st January 2017 to 30th November 2017. Total 64 patients were enrolled. Maternal and neonata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
2
1
0
Order By: Relevance
“…We found a significantly rising incidence of low birth weight babies among BMI more than or equal to 35mothers 83.3%. which is similar to Takai et al, 2017 [15] results which may be due to dysregulation of proinflammatory cytokines as well as increased risk of infection in obese and overweight individuals as they will lead to reduced placental surface area and also their vasculature with consequent uteroplacental insufficiency [16] In our study, we found more incidence of IUGR and NICU admissions in the BMI group more than or equal to 35, which is like Shah PM et al 2018 results [17] .…”
Section: Discussionsupporting
confidence: 90%
“…We found a significantly rising incidence of low birth weight babies among BMI more than or equal to 35mothers 83.3%. which is similar to Takai et al, 2017 [15] results which may be due to dysregulation of proinflammatory cytokines as well as increased risk of infection in obese and overweight individuals as they will lead to reduced placental surface area and also their vasculature with consequent uteroplacental insufficiency [16] In our study, we found more incidence of IUGR and NICU admissions in the BMI group more than or equal to 35, which is like Shah PM et al 2018 results [17] .…”
Section: Discussionsupporting
confidence: 90%
“…28 Various Indian and international studies depicting similar results were found. [29][30][31] Also, we found higher odds for preterm, macrosomia, IUFD and NICU admissions in study group. In a cohort study by Doi relation between high maternal BMI and pregnancy outcome was studied.…”
Section: Resultssupporting
confidence: 58%
“…33,34 Studies by Doi et al, Su et al, Castillejos et al, and Melchor et al also endorses similar results. 29,[30][31][32]35…”
Section: Resultsmentioning
confidence: 99%